The Influence of Insurance Services Marketing on Customer Behavior: A Case Study of Algeria's CAAT Insurance Company - Tahar Djamat; Houari Moaredj (Dirassat Journal Economic Issue, 2024)
The research problem revolves around the nature of marketing applied in insurance institutions and its implications for their performance. It is crucial to understand the unique characteristics of insurance products and services, which differentiate them from other products. This understanding is essential for highlighting the role and importance of marketing in improving the performance and profitability of insurance companies. Effective marketing enables these companies to serve their customers optimally, a goal that can only be achieved by adopting marketing as a tool that effectively contributes to achieving these objectives.